Gravity Influences How We Expect a Cursor to Move. (January 2022) - Brenner, Eli; Houben, Milan; Schukking, Ties; Crowe, Emily M.
We expect a cursor to move upwards when we push our computer mouse away. Do we expect it to move upwards on the screen, upwards with respect to our body, or upwards with respect to gravity? To find out, we asked participants to perform a simple task that involved guiding a cursor with a mouse. It took participants that were sitting upright longer to reach targets with the cursor if the screen was tilted, so not only directions on the screen are relevant. Tilted participants' performance was indistinguishable from that of upright participants when the screen was tilted slightly in the same direction. Thus, the screen's orientation with respect to both the body and gravity are relevant. Considering published estimates of the ocular counter-roll induced by head tilt, it is possible that participants actually expect the cursor to move in a certain direction on their retina.